KECEPATAN MEMBACA EFEKTIF SISWA KELAS XI SMA NEGERI 2 TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Safitri, Diana Safitri; Razak, Abdul Razak; ', Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This study titled The Effective Reading Speed class XI student of SMA Negeri 2 Tembilahan, Indragiri Hilir Regency. The problem in the study of how fast effective reading is, there any difference in the effective speed reading samples per group, per rank, per ethnic, per department and per gender is. The method used is descriptive method, with a total sample of 146 students in class XI SMA Negeri 2 Tembilahan. Data collection techniques to provide a test reading paragraphs exposition, consisting of four topics, such as Religion, Sports, Education and Environment. Every topic paragraph exposition consists of 60-160 wpm. The time process of reading paragraph is calculated by the researchers. After that, the students were given a multiple choice test consisting of five questions and five answers per topic selection. Then researchers correcting students’ answer sh using the reading speed formula. To know there any difference is in the speed of reading per group of samples, per rank, per ethnic, calculated using ANOVA. Per department, and per gender, calculated using the t test. If ANOVA rejected, counting is used again with the t test. Based on the research, the result that (1) the speed of effective reading low category (2) the speed of effective reading per different sample group, science class in speed reading higher than social class, the reading speed of science class is low category and social class is very low category (3) The speed Effective reading per rank is different, the first is high category ranking and the second ranked low category, ranking third category is very low (4) The effective reading speed per ethnic is the same or no difference (5) the effective reading speed by different departments, the speed reading of science majors (141 , 27 as low category) is higher than the social majors (114.99 as very low category) (6) effective reading speed per gender, women effective speed reading higher 136.86) than men (120.67) but as same as low category. Overall, it can be concluded that the effective speed reading class XI student of SMAN 2 Tembilahan Indragiri Hilir Regency has low category which is between 120-150 wpm. Keywords: Effective Reading Speed